Study of calcium implanted GaN - Alves, E.
Single crystalline GaN samples were implanted with several fluences of Ca ions at room temperature (RT) and 550 °C. The implantation at high temperature reduces significantly the damage. The measured minimum yield along the 〈0 0 0 1〉 axis in the implanted region increases from 15% to 40% when the substrate temperature during the implantation was changed from 550 °C and RT. The lattice site location was analysed simultaneously by measuring channeling effect on the backscattering particles and the particle-induced X-ray emission. Despite the different damage level, the regular fraction of Ca atoms in GaN lattice in both implantation conditions was roughly the same directly after the implantation (fs ∼ 50%), as indicated by the angular scans. Annealing at 1050 °C for 15 min in flowing N2 results in a significant recovery of the damage, but no changes were found for the Ca profile. The angular scans along the 〈0 0 0 1〉 and 〈1 0 1̄ 1〉 axial directions indicate that Ca is occupying mainly interstitial sites